Peran Financial Self-Efficacy dalam Memediasi Pengaruh Sikap Keuangan terhadap Pengelolaan Keuangan Pribadi pada Generasi Z: Denpasar - Made Ayu Desy Geriadi; Putu Lidia Marini (Widya Manajemen, 2026)
Generation Z faces challenges in managing their finances effectively amid digital lifestyle shifts, rapid technological development, and increasing access to financial services. A positive financial attitude is expected to encourage individuals to manage their finances wisely; however, poor financial practices among Generation Z are still commonly found. This study aims to analyze the influence of financial attitude on personal financial management, as well as the mediating role of financial self-efficacy among Generation Z in Denpasar City. This research adopts a quantitative approach by distributing questionnaires to 120 Gen Z respondents aged 18–27 years. Data were analyzed using regression and mediation tests through SEM PLS. The results show that financial attitude has a positive and significant influence on personal financial management. Financial self-efficacy also positively affects personal financial management and is proven to mediate the influence of financial attitude on personal financial management. These findings indicate that confidence in managing finances is a crucial psychological factor that strengthens the relationship between financial attitude and financial management ability. This study is expected to serve as a reference for developing financial education programs that focus not only on conceptual understanding but also on strengthening individuals' confidence in managing finances.